2014
DOI: 10.1016/j.chb.2014.09.045
|View full text |Cite
|
Sign up to set email alerts
|

Emotional disclosure on social networking sites: The role of network structure and psychological needs

Abstract: a b s t r a c tWe conducted three studies to understand how online emotional disclosure is influenced by social network structure on Facebook. Results showed that emotional disclosure was associated with both the density and size of users' personal networks. Facebook users with denser networks disclosed more positive and negative emotions, and the relation between network density and emotional disclosure was mediated by stronger need for emotional expression. Facebook users with larger networks on Facebook dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
99
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 124 publications
(112 citation statements)
references
References 103 publications
(100 reference statements)
6
99
2
2
Order By: Relevance
“…As the motivation for self-expression and freedom of control have been found to result in stronger cues for personality (Gosling et al, 2002), selfies may provide a better view of their owners' personality traits than other photos. However, studies have shown that individuals are likely to be concerned about their online self-image and manipulate their self-presentation to create socially desirable self-image (Bazarova, Taft, Choi, & Cosley, 2013;Ellison, Heino, & Gibbs, 2006;Lin, Tov, & Qiu, 2014;Qiu, Lin, Leung, & Tov, 2012;Strano, 2008). They have been found to promote themselves and obtain positive feedback from their social networks via profile pictures (Manago, Graham, Greenfield, & Salimkhan, 2008;Mehdizadeh, 2010;Siibak, 2009;Zhao, Grasmuck, & Martin, 2008).…”
Section: Personality Expression In Photosmentioning
confidence: 97%
“…As the motivation for self-expression and freedom of control have been found to result in stronger cues for personality (Gosling et al, 2002), selfies may provide a better view of their owners' personality traits than other photos. However, studies have shown that individuals are likely to be concerned about their online self-image and manipulate their self-presentation to create socially desirable self-image (Bazarova, Taft, Choi, & Cosley, 2013;Ellison, Heino, & Gibbs, 2006;Lin, Tov, & Qiu, 2014;Qiu, Lin, Leung, & Tov, 2012;Strano, 2008). They have been found to promote themselves and obtain positive feedback from their social networks via profile pictures (Manago, Graham, Greenfield, & Salimkhan, 2008;Mehdizadeh, 2010;Siibak, 2009;Zhao, Grasmuck, & Martin, 2008).…”
Section: Personality Expression In Photosmentioning
confidence: 97%
“…16,17 Due to self-representational concerns, they selectively disclose more positive than negative emotions to present a positive selfimage. 16,18 This desire to make a positive impression on others may reduce individual differences in the expression of positive emotion on Facebook, weakening the association between the latter and self-reported SWB. In contrast, because there is relatively less social pressure to express negative emotion (vs. positive emotion), such expressions are more likely to reflect how a person actually feels.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the process of building a prototype can significantly enhance communication skills and problem-solving skills. The team-based IT prototyping enhances the communication skills that is in line with (Lin, et al, 2014) and (Wang, et al, 2014). However, the course does not significantly improve the analytical skills contradicting the findings in (Aesaert & Braak, 2014) that used pupils as the research subjects.…”
Section: Discussion Limitations and Future Researchmentioning
confidence: 43%
“…Wang, et al (2014) discovered that some types of social network sites (SNS) have a positive effect on users' well-being, but do not improve the quality of friendship among college students. Lin, et al (2014) analyzed Facebook emotional disclosure and found that users with denser networks disclosed more positive and negative emotions, although the amount of disclosure was also mediated by the need for emotional expression.…”
Section: Related Workmentioning
confidence: 99%